2017
DOI: 10.1111/asj.12873
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings of Japanese Black Cattle living in the restricted area of the Fukushima Daiichi Nuclear Power Plant accident, 2013–2016

Abstract: Fifty-one Japanese black cattle from four farms in the evacuation zone of the Fukushima nuclear accident were examined pathologically during the period, 2013-2016. We found no evidence of a radiation effect on pathological findings in any of these autopsy cases, although nine cases (3.7%) of enzootic bovine leukosis (EBL) and three cases (1.2%) of goiter were diagnosed. Estimated integrating dose of external exposure in EBL cases ranged from a maximum of 1200 mSv to a minimum of 72 mSv. Clinically, five cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Five cases exhibited wobble, paralysis, or dysstasia and three cases showed exophthalmos. For all these cases, the diagnosis was enzootic bovine leucosis (Sasaki et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five cases exhibited wobble, paralysis, or dysstasia and three cases showed exophthalmos. For all these cases, the diagnosis was enzootic bovine leucosis (Sasaki et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 241 Japanese Black cattle were raised in 4 farms in the restricted area of the Fukushima Prefecture after the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident. The farms were located within a 20 km radius of the FDNPP (Sasaki et al, ). Farms A, C, and D were located in the town of Namie, whereas farm B was located in Okuma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, pathological research of Japanese black cattle living in the same evacuation zone revealed that there was no significant relationship between the radiation effect and incidence of tumors. 32 Thus, we expect that radiation exposure is not likely related to the tumorigenesis of the gallbladder carcinoma in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al detected 3678 ± 618 or 1874 ± 289 Bq/kg of radioactive cesium (total of 134 Cs and 137 Cs) in Farm A cattle thyroid (dissected in May or December 2014, respectively) 4 . Sasaki et al pathologically diagnosed that, among 66 cattle dissected in 2013–2017, there were 3 cattle with goiter and 7 cattle with atrophic thyroid without malignant findings 5 , 6 . Since there was no correlation between the level of exposure and the pathological changes, we concluded that radiation exposure is not the cause of these diseases.…”
Section: Introductionmentioning
confidence: 99%